Chaperonin-mediated protein folding 1 - Horwich, Arthur (Henry Stewart Talks, 2012)
Chaperonin-mediated protein folding by GroEL/GroES, Folding of newly-translated protein, Currently known Molecular chaperones (including the Heat shock protein Hsp group), Recognition of non native proteins by Hsps and formation of aggregates, Aggregates and neurodegenerative disease -The discovery of the chaperonin-mediated folding, The structure of the GroES/GroeEL chaperonin class of molecular chaperones, The steps of polypeptide binding and folding, The action of ATP binding and hydrolysis in driving the rings of the machine through cycles of binding and release cycle